Supervision of Madrasah Principals Based on Cognitive Behavior Therapy in Improving the Performance of Islamic Religious Education Teachers - Eliwati, Nur (Ruhama : Islamic Education Journal, 2023)
This study aims to determine the planning, implementation, evaluation, and follow-up of Cognitive Behavior Theraphy (CBT)-based supervision implemented by the madrasah head in improving the performance of Islamic Religious Education teachers. This research uses a qualitative descriptive approach, data collected through observation, interviews, and documentation studies. The results of the study are that planning is carried out referring to KMA 624 of 2021 and Kepdirjen Pendis Number 6335 of 2021. The implementation of CBT supervision is carried out using direct, indirect and collaborative approaches. Evaluation of CBT supervision is carried out by identifying the components of the supervision program implementation, including the results of supervision, lesson plan documents, implementation of teaching in the form of introductory activities, core activities, closing and reflection to find weaknesses and constraints of teachers in carrying out learning.